Therapeutic Drug Monitoring of Antidepressants: An Underused but Potentially Valuable Tool in Primary Care - Piacentino, Daria; Bianchi, Esperia; De Donatis, Domenico; Florio, Vincenzo; Conca, Andreas (Frontiers in Psychiatry, 2022)
Depressive disorders are among the most burdensome diseases globally in terms of prevalence, as well as in terms of quality of life, morbidity, and mortality. Hence, it is becoming increasingly common for primary care physicians to administer and monitor the treatment of individuals affected by depressive disorders. In this framework, Therapeutic Drug Monitoring (TDM) comes to the forefront. TDM is the measurement of specific drugs in the blood or plasma/serum, and its usefulness lies in the fact that it allows physicians to assess drug levels to personalize and optimize treatments. TDM has been used for decades to measure several classes of psychotropic drugs, such as antiepileptics and antipsychotics, but the use of this tool is still in its infancy in regard to antidepressants. In the context of primary care, TDM of antidepressant drug treatment shows promise, as it can enable primary care physicians to monitor the safety and efficacy of the treatment, leaving to secondary care, i.e., psychiatrists, the management of the more complex clinical cases.